BIOLOGICAL AND FUNGICIDAL MANAGEMENT OF CHICKPEA WILT CAUSED BY FUSARIUM OXYSPORUM F. SP. CICERI - V. B. PATIL,; D. B. GAWADE,; A. P. SURYWANSHI,; S. N. ZAGADE, (The Bioscan, 2015)
Chickpea (Cicer arietinum L), wilt caused by Fusarium oxysporum f. sp. ciceri is the most destructive disease in India and also first reported from India in 1918. It is seed-borne as well as soil-borne pathogen. Yield losses vary between 10% to 100% depending on varietal susceptibility and agroclimatic conditions. The results concluded that the significantly highest reduction in growth of the pathogen was induced by Trichoderma viride (15.3%), followed by Trichoderma koningii (24.4%). The moderate inhibition was induced by Trichoderma harzianum (28.9%), Gliocladium virens (30.5%) which were statistically at par and could induce however significant inhibition over control (75.20%). The significantly highest germination was obtained with Carbendazim (77.66%) which was at par with seed treatment by Trichoderma viride (75.33%). However, the all doses of seed treatment with T. viride and fungicidal seed treatments have significantly improved germination (%), increased vigour index, dry matter production and number of pods produced per plant were significantly influenced. Whereas, all the fungicides were found to be significantly superior over control in checking the radial growth and sporulation of Fusarium oxysporum f. sp. ciceri. Among all the fungicides Carbendazim (22.41%) was significantly superior and was at par with Benomyl (21.4%), Thiram (31.42%) and Captan (31.82%). Very scarce sporulation was observed in Carbendazim, Benomyl, Thiram and Captan acted as antisporulant.